(untitled) - Shahidi, Fereidoon (Boca Raton, Fl., 2003)
The book reports the classification and nomenclature of phenolics, their occurrence in food and nutraceuticals, chelistry and applications, and nutritional and health effects. In addition, it describes antioxidant activity of phenolics in food and nutraceuticals as well as methods for analysis and quantification.
Keywords: Phenols,Food industry and trade